A chameleon hash authentication tree optimisation audit for data storage security in cloud calculation. (30th April 2020) - Bo, Yang
In order to improve the security of data storage in cloud calculation, a chameleon hash authentication tree optimisation audit method for data storage security in cloud calculation is proposed. First, an optimised public audit agreement is proposed. By storing homomorphic linear validator for user data on TPA sites, the response size of cloud storage server (CSS) is optimised. At the same time, the quasi-random function is used to optimise the query request to CSS; secondly, the chameleon hash and an improved chameleon authentication tree are used to perform efficient dynamic data updating on client data (cloud calculation) to support block-level updating and fine-grained updating; finally, through thorough security and performance analysis, it is clearly verified that the proposed method is safe and efficient.